Bioadsorção dos inibidores gerados no pré-tratamento da biomassa lignocelulósica em biorrefinarias - Ribeiro, Marina Barbosa Maluf (2020)
In the pretreatment stage of lignocellulosic biomass in biorefineries can release compounds that act as inhibitors of the enzymatic hydrolysis and alcoholic fermentation steps. Among the inhibitors, the phenolic compounds originated from lignin degradation can inhibit or deactivate the enzymes during the hydrolysis reaction, significantly impacting the overall yield of the conversion of biomass into soluble sugars. Therefore, new strategies that contribute to mitigate the negative effect of these inhibitors are necessary to enable the viability of future biorefineries. In this context, a potential strategy is the use of microbial biomass as a low-cost biosorbent for the removal of the phenolic compounds generated in the pretreatment stage. Thus, the aim of this work was to evaluate the use of Aspergillus niger microbial biomass for adsorption of the phenolic compounds present in the liquor of the hydrothermal pretreatment of sugarcane bagasse. The fungal cultivation was made to obtain the microbial biomass and three types of treatments (autoclave, acidic and basic solutions) were used to prepare the biosorbents. Tests with synthetic samples of vanillin (monomer) and tannic acid (oligomer) showed that the biosorbents have a greater affinity for adsorbing larger molecules, such as tannic acid, as it is a low porous material. The effect of the adsorbent load, pH and temperature on the adsorption capacity was also evaluated. A 98% removal of tannic acid was obtained by the biomass treated with sodium hydroxide, whereas for vanillin the affinity was lower, with a removal of just over 30%. For the total phenolics present in the pre-treatment liquor, a removal of around 40% was obtained. The enzymatic hydrolysis assays of the hydrothermal bagasse in the presence of the liquor after the removal of the inhibitors by the biosorbents showed a 50% increase in the glucose release. The results obtained indicate that the fungal biomass has an interesting potential for the removal of the inhibitors present in the liquor of the pretreatment of the sugarcane bagasse in order to improve the conversion of the sugars in the enzymatic hydrolysis stage in biorefineries.